Extending the shelf life of tahu, Indonesian soybean curd - Clucas, A. C. (Faculty of Food Science and Technology, Universiti Pertanian Malaysia, 2018)
Studies were undertaken to extend the shelf life of tahu, or soybean curd, a traditional product of Indonesian villagers. Freshly prepared tahu was given the fallowing treatments prior to storage in closed plastic containers at 30°C-, (soaking 2% formalin for 30 min, then drained; blanching for 2.5 min in boiling water; blanching for 1.5 min and 30 min and storing in boiled water; immersing in 0.1% potassium sorbate solution; immersing in 10% lemon juice containing 4% salt; blanching jar 5 min and storing in 10% lemon juice containing 4% salt. Samples were examined, after storage for up to 9 days, for pH, titratable acidity, microbial load, and organoleptic acceptability. Blanching combined with immersion in aqueous solution was effective in extending the shelf life of tahu. The most successful treatment was the 5 min blanch in boiling water followed by storage in an aqueous solution containing 10% lemon juice and 4% salt which gave a shelf life of about 5 days days at 30°C.